Evaluating the economic impact of clinical pharmacist interventions in the women’s health setting in Qatar - Daoud Al-Badriyeh (832403) (2025)
Background Adverse drug events (ADEs) resulting from nonoptimized medication therapy significantly drive-up healthcare costs. Clinical pharmacists are pivotal in managing medication regimens, effectively reducing these associated expenses. Aim Given the scarcity of similar studies in the region, this study aimed to evaluate the overall economic impact of clinical pharmacists’ interventions against ADEs at the Women’s Wellness and Research Center (WWRC) in Qatar. Method Analysis of the total economic benefit of clinical pharmacists’ interventions was performed through a retrospective chart review of patients’ records admitted during the periods of March 2018, July–August 2018, and January 2019. The current analysis was based on WWRC’s perspective, in which the cost savings and cost avoidance associated with the interventions were used to determine the total economic benefit. A sensitivity analysis was conducted to determine the robustness of the results. The study was approved at the main public healthcare provider. Results A total of 331 interventions for 162 patients were included in the analysis. The total economic benefit was estimated to be QAR169,320 (USD46,503), comprising cost avoidance of QAR170,995 (USD46,964) and negative resource-use cost savings of QAR-1675 (USD-460). The increase in resource use was primarily due to the addition of other medications to therapy. The sensitivity analysis confirmed that the outcomes are robust, demonstrating a 100% probability for positive economic benefits in all simulated cases. Conclusion Although there was an observed increase in resource utilization resulting from clinical pharmacists’ interventions, this study highlights their crucial role in mitigating the costs associated with preventable adverse drug events. Other Information Published in: International Journal of Clinical Pharmacy License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s11096-025-01933-z